Do leaders actually influence sports performance? An integrated systematic review and meta-analyses - Clare, C.; Hardy, J.; Roberts, R.; Tod, D.; Benson, A. (Journal of Sport & Exercise Psychology, 2025)
The precise nature of the leadership-sport performance relationship remains unclear. Furthermore, understanding of how leadership effects might differ across coach and athlete leaders or across team and individual performance is currently limited. To address these issues, we conducted an integrated systematic and meta-analytical review (50 studies, 17,158 athletes) to quantify differences between coach and athlete leaders and examine potential moderator variables. Results revealed a significant yet small positive relationship between leadership and performance (r = .21; Hedges` g = 0.44). Significantly stronger relationships emerged for team captains (r = .34) with team performance than coaches (r = .18) and informal athlete leaders (r = .15). Moreover, significantly larger effect sizes were yielded for authentic (r = .44) and transformational (r = .33) compared with social identity leadership (r = .19). In summary, both coaches and athletes possess the potential to be effective leaders who influence both team and individual performance.